The Implementation of Character Education in Elementary School: the Strategy and Challenge - Heru Handoko; E. Kus Eddy Sartono; Heri Retnawati (Jurnal Ilmiah Sekolah Dasar, 2023)
Elementary school is the most basic level of formal education for children, so character education is important at this level. Moreover, the negative impact of information disclosure and technological advancement has penetrated the behaviour of elementary school students. This study aims to analyse the strategies and challenges in implementing character education in several elementary schools based on general interpretations of practitioners' experiences in the field. This is a qualitative study with a phenomenological approach. The subjects of this study consisted of 5 principals, 27 class teachers, and 55 parents. Sampling in this study used snowball sampling technique. The data collection method used interviews. Data analysis, including: data display, data condensation, and conclusion drawing. The results of this study show that the implementation strategy of education in elementary schools, in the form of: character education implementation strategies through teaching and learning activities, extracurricular activities, exemplary, and habituation. Challenges faced by elementary schools in implementing character education include: incomplete school facilities, bad family conditions, and unsupportive community conditions. The conclusion of this study shows that: (1) elementary schools have not yet implemented a holistic character education implementation strategy, i.e. the implementation of character education through co-curricular activities; and (2) The main challenge of implementing character education in elementary schools is bad family conditions.